Citation practices in Malaysian research article introduction sections / Siti Raihan Shamsudin - Shamsudin, Siti Raihan (2015)
One of the elements that is important in academic writing, particularly in the research articles is citation. Citation is a common, persistent feature of written academic discourse in research articles in particular. In other word, the communication, enmasse, specifically communication within the discourse community which is effected vis a vis the citation to an author’s research included in any level of academic writing. This research investigated on the similarities and differences in the citation practices and choices of reporting verbs in Malaysian English Research Articles introduction sections from the Humanities and Social Sciences and, Sciences and Engineering. The data consisted of eighty corpora from eight different disciplines. Corpus was then analyzed based on Thompson and Tribble’s (2001) types of citations and Thompson and Ye’s (1991) categories of reporting verbs. Findings show significant differences whereby writers followed different strategies in employing non-integral and integral citation practices due to their specific citation conventions, discourse conventions and style conventions. Based on results of this study, lecturers of English for Academic Purposes (EAP) can understand the citation types and reporting verbs of choices employed in Humanities and Social Sciences RAs and compares them with those in Sciences and Engineering RAs. Moreover, seeing the differences between the disciplines in terms of citation practices and reporting verbs, they can develop the writing and research skills that are needed to use all citation types effectively so as to enhance students’ writing skill in producing quality academic papers.